A new proposal to guide velocity and inclination in the ramp protocol for the treadmill ergometer - Silva,Odwaldo Barbosa e (2003)
OBJECTIVE: To suggest criteria to guide protocol prescription in ramp treadmill testing, according to sex and age, based on velocity, inclination, and max VO2 reached by the population studied. METHODS: Prospective study describing heart rate (HR), time, velocity, inclination, and VO2 estimated at maximum effort of 1840 individuals from 4 to 79 years old, who performed a treadmill test (TT) according to the ramp protocol. A paired Student t test was used to assess the difference between predicted and reached max VO2, calculated according to the formulas of the "American College of Sports Medicine". RESULTS: Submaximal HR was surpassed in 90.1% of the examinations, with a mean time of 10.0±2.0 minute. Initial and peak inclination velocity of the exercise and max VO2 were inversely proportional to age and were greater in male patients. Predicted Max VO2 was significantly lower than that reached in all patients, except for female children and adolescents (age < 20 years old). CONCLUSION: Use of velocity, inclination, and maximum VO2 actually reached, as a criterion in prescribing the ramp protocol may help in the performance of exercise in treadmill testing. The ramp protocol was well accepted in all age groups and sexes with exercise time within the programmed 8 to 12 minutes.